KALKULASI OVERALL EQUIPMENT EFFECTIVENESS (OEE) UNTUK MENGETAHUI EFEKTIVITAS MESIN KOMATZU 80T (Studi Kasus pada PT. Yogya Presisi Tehnikatama Industri) - Sunaryo Sunaryo; Eko Ardi Nugroho (Faculty of Industrial Technology Universitas Islam Indonesia, 2015)
One of the molding injection Komatsu 80T in the PT Yogya Presisi Teknikatama Industry has a problem on its performance. The performance of this injecton molding can be calculated by Overall Equipment Effectiveness(OEE). OEE is a factor which can be found by multiplication of Availability Ratio, Performance Efficiency and Rate of Quality. The values of OEE then be compared to the standart values of JIPM (The Japan Institute of Plan Maintenance) which JIPM defined a minimal standard value of OEE is 85%. If the result of OEE calculation less than 85%,what causes it be analysed by the Six Big Losses Analysis. The Result of analysis showed the sequence as Reduced Speed Loss, Setup and Adjusmnet loss, and Rework Loss. Then by Fishbone diagram, it can be known the causes of the decreasing OEE values, so the management can do the repairment.